Republic of San Marino : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
This Selected Issues paper describes the developments and challenges in the financial sector of the Republic of San Marino. The study analyzes the structure of the financial sector, compares the performance of Sammarinese banks with those in other countries, reviews the legal and regulatory environment as well as supervisory practices, and discusses the challenges facing the banking system. The paper also provides the statistical appendix report for the country.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet